2021
DOI: 10.1155/2021/4485618
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of the Dynamic Electrocardiogram in the Elderly with Nonvalvular Atrial Fibrillation Combined with Long R-R Intervals

Abstract: Objective. To investigate the characteristics of dynamic electrocardiogram and their clinical implications in elderly patients with nonvalvular atrial fibrillation combined with long R-R intervals. Methods. Elderly patients diagnosed with nonvalvular atrial fibrillation who were admitted as an inpatient or attended the outpatient department from January 2015 to January 2020 were selected. Patients were divided into two groups based on the presence of a long R-R interval. The characteristics and therapeutic sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The heart rate is reciprocally associated with the RR-interval (QRS-to-QRS interval) [ 21 ]. The presence of long RR-intervals may worsen CHD (coronary heart disease) and HF (heart failure), as well as elevating the SBP [ 22 ]. The recordings of the non-invasive SBP ( Figure 1 ) and RR-interval ( Figure 2 ) in this experiment on day 7 as compared to day 0 in all of the groups corroborate with the earlier reports of L-NAME administration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heart rate is reciprocally associated with the RR-interval (QRS-to-QRS interval) [ 21 ]. The presence of long RR-intervals may worsen CHD (coronary heart disease) and HF (heart failure), as well as elevating the SBP [ 22 ]. The recordings of the non-invasive SBP ( Figure 1 ) and RR-interval ( Figure 2 ) in this experiment on day 7 as compared to day 0 in all of the groups corroborate with the earlier reports of L-NAME administration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RR interval, denoting the time between consecutive R waves in the QRS signal, is a critical parameter for assessing ventricular rate. In healthy individuals, normal ECG values for the RR interval typically range between 0.6 and 1.2 s. Prolonged RR intervals, defined as > 1.5 s, are commonly observed in patients with atrial fibrillation [37].…”
Section: Feature Extractionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%